2013
DOI: 10.1097/crd.0b013e31827ed0c9
|View full text |Cite
|
Sign up to set email alerts
|

A New Potential Approach to Inotropic Therapy in the Treatment of Heart Failure

Abstract: Urocortins (UCNs), peptides that belong to the corticotrophin-releasing hormone family, represent a novel group of inotropic agents that have a multifaceted effect on the body with significant effects on the cardiovascular, hemodynamic, neurohormonal, and renal systems. UCNs can potentially improve the overall picture of heart failure by targeting not only the cardiovascular and hemodynamic systems like many current inotropic agents but also other systemic tissues that contribute significantly to the mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
(20 reference statements)
0
5
0
2
Order By: Relevance
“…Due to its potential to become a marker of HF, Ucn-2 is still undergoing tests on both models. A study on a group of eight healthy men confirmed the hemodynamic effect, as well as the ability to decrease MAP and vascular resistance and increase the left ventricular ejection fraction [85]. In a combined clinical and experimental study, Ucn-2 was able to decrease PAH, improve right ventricle function, and improve pulmonary circulation [86].…”
Section: (D) Urocortin-2mentioning
confidence: 81%
“…Due to its potential to become a marker of HF, Ucn-2 is still undergoing tests on both models. A study on a group of eight healthy men confirmed the hemodynamic effect, as well as the ability to decrease MAP and vascular resistance and increase the left ventricular ejection fraction [85]. In a combined clinical and experimental study, Ucn-2 was able to decrease PAH, improve right ventricle function, and improve pulmonary circulation [86].…”
Section: (D) Urocortin-2mentioning
confidence: 81%
“…In general, the changes in Ucn III in Groups B and C could represent a local protective mechanism to stressful stimuli, although we could not draw conclusions on whether the expression changes in the ligands and receptors is a compensatory rather than a causative mechanism. Further studies in larger groups could clarify its involvement in fetal development and pathology, especially as urocortins have recently been identified as a new group of inotropic factors with multiple and important effects on the cardiovascular, hemodynamic, neurohormonal and renal system 51,52 and possibly novel players in the pathophysiology of the heart and its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of these hormones to CRF-R2 receptors causes activation of several second messenger cascades leading to peripheral vasodilation, inotropic and chronotropic effects, anti-inflammatory effects, and anti-ischemic effects. 74,75 In patients with stable HF as well as with AHF, infusion of urocortin-2 has been shown to increase cardiac output (CO), decrease SVR, and decrease PCWP, although the latter observations were not statistically significant. 76,77 Similar hemodynamic findings have been observed following administration of human stresscopin to patients with stable HFrEF and low CO without significant effects on SBP.…”
Section: Investigational Drugs For Acute Hfmentioning
confidence: 99%